Melanchthons Konzeption der Verträge Archäologie der Privatautonomie - Schmoeckel, Mathias 1963- (2018)
The Concept of Contracts. Melanchthon and the Freedom of Contracts. This article explores the significance of Melanchthon for the development of modern contract doctrine. In 1521 and 1525 Melanchthon regarded private settlements as the sole way for free and equal subjects to create binding law among them. Although his reasoning was the necessary fruit of his theology, he drew on Aristotle to enhance the persuasiveness of his argumentation. The result was the quest for a general term for binding agreements. In order to prove Melanchthon's crucial role, the slow development towards a new "contract" law has to be ascertained with regard to the precursors in theology, philosophy, and law - both Roman and Canon jurisprudence. The reception of Melanchthon demonstrates once again the original gap between the jurisprudence of Catholic and Protestant states
Keywords: Melanchthon, Philipp -- 1497-1560; Recht; Geschichte; Kirchenrecht; Evangelische Kirche; Werkanalyse